Barriers and facilitators to mobile health and active surveillance use among older adults with skin disease. (30th June 2021) - Johnson, Austin; Shukla, Neha; Halley, Meghan; Nava, Vanessa; Budaraju, Janya; Zhang, Lucy; Linos, Eleni
Abstract: Background: The COVID‐19 pandemic has accelerated the adoption of telemedicine, including teledermatology. Monitoring skin lesions using teledermatology may become increasingly important for several skin diseases, including low‐risk skin cancers. The purpose of this study was to describe the key factors that could serve as barriers or facilitators to skin disease monitoring using mobile health technology (mHealth) in older adults. Methods: Older adult dermatology patients 65 years or older and their caregivers who have seen a dermatologist in the last 18 months were interviewed and surveyed between December 2019 and July 2020. The purpose of these interviews was to better understand attitudes, beliefs and behaviours that could serve as barriers and facilitators to the use of mHealth and active surveillance to monitor low‐risk skin cancers. Results: A total of 33 interviews leading to 6022 unique excerpts yielded 8 factors, or themes, that could serve as barriers, facilitators or both to mHealth and active surveillance. We propose an integrated conceptual framework that highlights the interaction of these themes at both the patient and provider level, including care environment, support systems and personal values. Discussion and conclusions: These preliminary findings reveal factors influencing patient acceptance of active surveillance in dermatology, such as changes to the patient‐provider interaction and alignment with personal values. These factors were also found to influence adoption of mHealth interventions. Given such overlap, it is essential to address barriers and facilitators from both domains when designing a new dermatology active surveillance approach with novel mHealth technology. Patient or public contribution: The patients included in this study were participants during the data collection process. Members of the Stanford Healthcare and Denver Tech Dermatology health‐care teams aided in the recruitment phase of the data collection process.